„Nie myślę, lecz jestem”: mózg, umysł i serce filmowej postaci zombie w kontekście paradygmatu posthumanistycznego - Nowakowski, Jacek (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article presents the character of the zombie popular in the contemporary audio-visual culture by placing it in the context of post humanist paradigm. He concentrates on the brain symbolism representative for the character, which, in the classical understanding of the living dead, due to dissimilar functioning, makes it different from humans and their brain-like traits: the mind and heart. Analysing the recent films such as Warm Bodies and The Girl with All the Gifts, he demonstrates the present inadequacy of such a division. Unlike the classical Night of the Living Dead, they are in line with post anthropocentric and new materialism philosophy, by differently symbolically depicting the role and place of the human in the world. It is presently tantamount to the place of non-humans: animals, objects, artefacts and monsters including the living dead. The change of the cultural and film paradigm observed in zombie horrors indicates a deeper strategy of authors of those popular films.